Norm's trust model to evaluate norms benefit awareness for norm adoption in an open agent community - Itaiwi A.K.; Ahmad M.S.; Tang A.Y.C. (Science and Information Organization, 2023)
In recent developments, norms have become important entities that are considered in agent-based systems' designs. Norms are not only able to organize and coordinate the actions and behaviour of agents but have a direct impact on the achievement of agents' goals. Consequently, an agent in a multi-agent system requires a mechanism that detects specific norms for adoption while rejecting others. The impact of such norms selection imposes risks on the agent's goal and its plan ensuing from the probability of positive or negative outcomes when the agent adopts or reject some norms. In an earlier work, this predicament is resolved by enabling an agent to evaluate a norm's benefits if it decides to adopt a particular norm. The evaluation mechanism entails a framework that analyzes a norm's adoption ratio, yield, morality and trust, the unified values of which indicates the norm's benefits. In this paper, the trust parameter of the mechanism is analyzed and a norm's trust model is proposed and utilized in the evaluation of a norm's benefits for subsequent adoption or rejection. Ultimately, the norm's benefits are determined as a consequence of a favorable or unfavorable trust value as a significant parameter in a norm's adoption or rejection. 2015 The Science and Information (SAI) Organization Limited.